1990
DOI: 10.1103/physrevlett.64.2458
|View full text |Cite
|
Sign up to set email alerts
|

Complete elastic constants and giant softening ofc66in superconductingLa1.86

Abstract: A novel resonant ultrasound technique is used to measure all elastic constants and their temperature dependence in single-crystal Lai 86Sro 14CUO4. The in-plane shear modulus C66 drops by nearly half upon cooling to 227 K, an effect attributed to order-parameter fluctuations (of 2D Gaussian character) near the tetragonal-orthorhombic phase boundary. Implications for current models of the structural phase transition are discussed, as well as the effect of domains in the low-temperature orthorhombic state.PACS n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
28
0

Year Published

1991
1991
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(28 citation statements)
references
References 17 publications
0
28
0
Order By: Relevance
“…There is a substantial Curie-Weiss-like softening of c 66 as the HTT-LTO transition is approached from above, and the quality factor Q is also substantially reduced. This was initially interpreted in terms of critical fluctuations [564]. However, the softening persists to very high temperatures, 80K above the HTT-LTO transition, much higher than a theoretical estimate for fluctuations.…”
Section: B Short-range Order and The Dynamical Jt Phasementioning
confidence: 99%
See 1 more Smart Citation
“…There is a substantial Curie-Weiss-like softening of c 66 as the HTT-LTO transition is approached from above, and the quality factor Q is also substantially reduced. This was initially interpreted in terms of critical fluctuations [564]. However, the softening persists to very high temperatures, 80K above the HTT-LTO transition, much higher than a theoretical estimate for fluctuations.…”
Section: B Short-range Order and The Dynamical Jt Phasementioning
confidence: 99%
“…Moreover, throughout the LTO phase the elastic properties remain anomalous; c 66 remains soft, and Q is reduced by a factor of ∼ 100 [564,566]. This is assumed to be caused by martensitic-like domain wall motion.…”
Section: B Short-range Order and The Dynamical Jt Phasementioning
confidence: 99%
“…16 The small ratio of two interactions, J / V ph Ϸ t / U 1 or J / V ph Ϸ V c / U 1, and the giant sound-speed anisotropy 17,18 favor conventional EPI as the origin of the unconventional pairing both in underdoped cuprates, where the pairing is individual, 14 and in overdoped samples apparently with Cooper pairs. 3 Nowadays, compelling evidence for a strong EPI has arrived from isotope effects, 22 more recent high resolution angle resolved photoemission spectroscopies, 23 and a number of earlier optical, [24][25][26][27] neutron-scattering, 28 and recent inelastic scattering measurements 29 in cuprates.…”
mentioning
confidence: 99%
“…However, in the case of La 2-x Sr x CuO 4 (LSCO) some experiments have been realized. Migliori et al [1] reported the measurement of all the elastic constants in compounds with x=0.1 and 0.14. They noticed a giant softening of the c 66 coefficient at the tetragonal to orthorhombic transition.…”
mentioning
confidence: 99%